Avant-garde modernism in the sacred architecture of Central Europe - Gnatiuk, Liliia (Theory and practice of design, 2022)
Iconic temples of the 20th century were analyzed. — the churches of Volker Hienke (Church of Eigen, 1990–1992, Ennstal, Austria), Josef Gochar (Church of St. Wenceslas, 1926–1927, Prague) and Aladar Arkaj (Church of the Sacred Heart of Jesus, 1932–1933, Budapest), which are mentioned together as examples of avant-garde modernist sacred architecture of Central Europe. The anthroposophical theory of architecture is presented, which assumed that the world and man are permeated by various types of spiritual forces, which can be strengthened or weakened thanks to the forms of objects of the visible world. The understanding of the harmony of forms in shaping the sacred space is represented, as well as the use of their anti-individualistic potential for the revival of social and religious communities. The architecture of sacred buildings built according to the principle of classical architecture is considered. It has been determined that the forms created by Volker Hienke, Josef Gochar and Aladar Arkai do not belong to any of the “languages” of architectural expression that have been created so far. A look at the mysterious nature of connecting people in society is presented — close to the types of ties that bind religious communities, as well as the concept of architecture as a bridge between heaven and earth, which also changed the approach to the building as an exclusively material object. The forms of the sacred building and the way of organizing the interiors were analyzed, which made it possible to conclude that the ideas of reviving the unity of the surrounding landscape, the tendency to use local materials (primarily stone), but also a more general, philosophical attitude, which allows considering architecture as an element that connects the forces of the cosmos with human life, which unites believers of different faiths. The considered use of the metaphorical language of architecture is based on the world of visual human products and their iconographic distinctive features. The need to take into account the relationship between certain forms and the messages transmitted through them in shaping the sacred space has been revealed. An attempt to adapt the principles of modernism to the needs of shaping the sacred space is also presented. It was found that the problems of the formation of a new style arose as a result of changes in the architecture itself, and difficulties in determining its characteristic features — as a result of changes in historiography. The trends in the shaping of the sacred space in the 20th century were revealed.